La aplicación del Principio de Interdicción de la Arbitrariedad y su incidencia en las resoluciones en los Procedimientos Sancionatorios adoptadas por el departamento de Turismo del GAD Municipal Riobamba durante el año 2020. - Martinez Villacres, Tanya Dolores (2023)
ABSTRACT: The current research is proposed to systematize the demands that derive from the principle of interdiction of arbitrariness and its materialization in the sanctioning administrative procedure, with the objective of characterizing it as a limit to the punitive state´s power in the determination of administrative responsibility and application of sanction. Due to the fact that the decentralized autonomous governments are part of the public administration and have political, administrative, and financial autonomy, they pursue sanctioning power and have the competence to apply certain sanctions when an administrative infraction is committed. For this reason, it is necessary to establish that the interdiction of arbitrariness principle imposes limits on the authorities and institutions of the public administration to protect the rights and basic freedoms of the administered. This issue is being addressed in the study of the sanctioning administrative management process of the Department of Tourism of the Municipal GAD in Riobamba. A qualitative methodology of explanatory scope is used, applying inductive-deductive methods, exegetical analysis, and documentary analysis. The main expected result is the proper application of the principle in the sanctioning administrative procedure established in the Organic Administrative Code for a better protection of the rights of those administered in the sanctioning administrative procedure established in the Administrative Organic Code, which will have a positive impact on the guarantees of the rights of persons subject to the sanctioning power of the Ecuadorian public administration. In this work, the problem will be investigated from the administrative field in order to establish if the interdiction of arbitrariness in administrative procedures principle is adequately applied